До питання про заснування міста Карлівка Полтавської області - Пилипець, В. (Краєзнавство, 2018)
У статті йдеться про козацький період передісторії майбутньої Карлівщини, який пов'язаний з
постатями старшинської еліти суддею Полтавського полку Іваном Красноперичем та полковим обозним Климентієм Нащинським. Розкривається визначна роль генерал-аншефа Іоганна-Бернгарда Вейсбаха та справжнє місце в історії Карлівки його наступника фельдмаршала Бурхада-Христофа Мініха.
Обґрунтовується реальна дата початку відліку історії сучасного міста – жовтень 1731 року. Висвітлюються обставини переходу Карлівщини у власність сімейства Розумовських та результати їхнього
господарювання. Вперше піднімається питання щодо місця і ролі Карлівки на початковому етапі розбудови Української оборонної лінії. The basis of the article was the long-standing documentary studies carried out by the initiative group of
the Karlivka residents on the real circumstances of the emergence and rapid development of the former huge
Karlivkaestate and its organic center – themodern town of Karlivkain Poltava region. This material has never
been published before and remains unknown to a wide range of the history of Ukraine researchers. The information
contained in the article significantly differs from that reported in such general publications as «History
of the Cities and Villages of the Ukrainian SSR» (K., 1967) and «Poltava Region: Encyclopedic Directory» (K,
1992) «Encyclopedia of Contemporary Ukraine. Volume 12» (K., 2012) and contains their critical assessment,
which is based solely on a documentary basis.
The article deals with the Cossack period of the pre-history of the future Karlivka region, which is connected
with the figures of the eldership elite such as the judge of the Poltava regiment Ivan Krasnoperych and the regimental
defender Clement Nashchinskyi. The prominent role of General-Anchef Johann-Bernhard Weisbach
and the true place in Karlivka’shistory his successor Field Marshal Burhad-Christoph Minich, are revealed.
The actual date October 1731is substantiated as the beginning of the modern townhistory. The circumstances
of the transition of the Karlivka region to the ownership of the Rozumovsky’s family and the results of their
management are highlighted in the article. The issue of Karlivka’s place and role at the initial stage of building
the Ukrainian Defense Line is raised for the first time. В статье представлена информация, касающаяся ранней истории Карловщины, истории возникновения городка Карловка и первых годов его существования как центра карловских владений.